Secret war in the Pacific Peter Parsons and Moon River Productions. - Parsons, Peter; Cavett, Morgan; Anderson, John; Guillermo, Lucky; Leese, Howard; Nevil, Steve (Peter Parsons ; Moon River Productions, 2006)
The story of Commander Charles "Chick" Parsons, the man General Douglas MacArthur called the bravest man he had ever known.